New legal approaches to studying the Court of Justice : revisiting law in context - Kilpatrick, Claire; Scott, Joanne (Oxford : Oxford University Press, 2021)
This title provides tools and approaches to study the activities of the European Court of Justice. Using new primary sources and an interdisciplinary approach, it develops a more holistic methodology for studying law and courts, especially the Court of Justice.
This edition previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 6, 2021).
Keywords: Court of Justice (Court of Justice of the European Union); Law -- European Union countries -- Study and teaching